Single-Particle Radiation Sensitivity of Ultrawide-Bandgap Semiconductors to Terrestrial Atmospheric Neutrons - Daniela Munteanu; Jean-Luc Autran (Crystals)
Semiconductors characterized by ultrawide bandgaps (UWBGs), exceeding the SiC bandgap of 3.2 eV and the GaN bandgap of 3.4 eV, are currently under focus for applications in high-power and radio-frequency (RF) electronics, as well as in deep-ultraviolet optoelectronics and extreme environmental conditions. These semiconductors offer numerous advantages, such as a high breakdown field, exceptional thermal stability, and minimized power losses. This study used numerical simulation to investigate, at the material level, the single-particle radiation response of various UWBG semiconductors, such as aluminum gallium nitride alloys (AlxGa1−xN), diamond, and β-phase gallium oxide (β-Ga2O3), when exposed to ground-level neutrons. Through comprehensive Geant4 simulations covering the entire spectrum of atmospheric neutrons at sea level, this study provides an accurate comparison of the neutron radiation responses of these UWBG semiconductors focusing on the interaction processes, the number and nature of secondary ionizing products, their energy distributions, and the production of electron–hole pairs at the origin of single-event effects (SEEs) in microelectronics devices.